Hammy's house: and other story poems - Foster, John (Oxford University Press Oxford, 1992)
This collection of poetry has been specially selected for Year 3 of the National Curriculum by children's author and anthologist John Foster. The poets featured include Finola Akister, Tony Bradman and Moira Andrew.